Trichodysplasia Spinulosa: Rare Presentation of Polyomavirus Infection in Immunocompromised Patients. Issue 6 (November 2014) - Kirchhof, Mark G.; Shojania, Kam; Hull, Mark W.; Crawford, Richard I.; Au, Sheila
Background: Trichodysplasia spinulosa (TS) is a rare, striking, folliculocentric papular eruption seen exclusively in immunosuppressed patients. The eruption can be disfiguring, associated with leonine faces and alopecia. TS is caused by a polyomavirus, identified as trichodysplasia spinulosa polyomavirus (TSPyV). Few reports exist in the literature, and support for treatment options is sparse. Method and Results: We report a patient with TS with underlying lupus nephropathy and renal transplant–associated immunosuppression. Diagnosis was confirmed by biopsy and pathognomonic histologic findings in the context of her extensive, spiculated monomorphous papules. With a biopsy-confirmed diagnosis, oral valganciclovir was prescribed, and the patient showed marked skin texture improvement and hair regrowth. Conclusion: The continued reporting of cases of TS will improve clinical identification of this condition and provide better information regarding treatment and long-term consequences.